Comparing the Efficiency of Different Approaches to Teach Informatics at Secondary Schools - Christoph STEER; Peter HUBWIESER (Informatics in Education, 2010)
Each of the 16 federal states of Germany has its own school system and also its own policy to integrate informatics, computer science or ICT into this system. Till present there aren't any tests of students' knowledge on a nation-wide level. Therefore nation-wide or international contests currently offer the only opportunities to compare the knowledge of the participating students on a large scale level. By evaluating the overall performance of the students of different federal states, we were able to compare the effectiveness of different approaches of teaching Informatics at secondary schools.